How to fulfill the expert role in public dialogue: The Dutch dialogue on human germline genetic modification as a case - Reincke, Cathelijne M.; Bredenoord, Annelien L.; van Baalen, Sophie; van Mil, Marc H. W. (Frontiers in Communication, 2022)
Over the last decades science communication theory appears to have evolved at a much faster pace than science communication practice. Scientists seem willing to step into the public domain, but a genuine two-way interaction with the public is only rarely observed. We argue that part of this discrepancy between theory and practice may actually be caused by the lacking of a clear description of the modern expert role; the role a scientist should take in contemporary science communication. In this contribution we use an example of good practice - the Dutch dialogue on human germline genetic modification - to inform theory. We analyze guiding principles for the design and execution of this dialogue and observe expert behavior in three separate dialogue sessions. With the combined findings, we present a detailed description of the modern expert role in terms of three responsibilities, with for each responsibility three prompts for behavior. For the responsibility to share these are to select expert knowledge that is relevant to the goal; to present expert knowledge in a meaningful and accessible language; and to be cautious in sharing personal considerations. For the responsibility to listen and learn these are to consider interactions with members of the public as opportunities to learn; to be patient and supportive; and to assist in stimulating in-depth dialogue. For the responsibility to invest in relationships these are to assist in creating an ambiance of safety and relevance; to preserve trust; and to convey respect for all dialogue partners and every contribution. Each behavioral prompt is further concretized with concomitant actions and practice examples as collected from observing experts in action. The implications for scientists engaging in contemporary science communication, as well as for science communication trainers, are discussed.